2011
DOI: 10.1007/dcr.0b013e3181fd677d
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Lymph Node Ratio After Neoadjuvant Chemoradiation and Rectal Cancer Surgery

Abstract: Patients who undergo neoadjuvant chemoradiation before rectal cancer surgery frequently have fewer than 12 lymph nodes harvested despite maintaining vigorous surgical standards. Lymph node ratios may provide excellent prognostic value and are possibly a better independent staging method than absolute positive lymph node counts when less than 12 lymph nodes are harvested after neoadjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 21 publications
1
18
0
2
Order By: Relevance
“…Because this study was not prospectively designed, it is subject to potential bias. The cutoff value of LNR is different from other studies (Kang et al, 2011;Klos et al, 2011;La et al, 2013;Madbouly et al, 2013;Nadoshan et al, 2013). In fact, the cutoff value varies among different studies, ranged from 0.07 to 0.6 (Madbouly et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…Because this study was not prospectively designed, it is subject to potential bias. The cutoff value of LNR is different from other studies (Kang et al, 2011;Klos et al, 2011;La et al, 2013;Madbouly et al, 2013;Nadoshan et al, 2013). In fact, the cutoff value varies among different studies, ranged from 0.07 to 0.6 (Madbouly et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…The remaining 21 studies were reviewed with full texts, among which two studies had unclear reporting of neoadjuvant therapy, one lacked endpoint data, and five lacked comparison between LNR groups. Finally, 13 studies with 4023 participants were included in the meta‐analysis, and all were published in recent years (from 2011 up to now). Table offers the baseline characteristics of all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…OS, as the primary outcome, was extracted from 11 studies with available data. Among them, eight studies reported high and low LNRs with one cut‐off value, and a pooled HR of 2.94 (95% CI:1.97 to 3.91, P < 0.001) demonstrated that a high LNR is a predictor of poor OS in rectal cancer after neoadjuvant therapy (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8] Peng and colleagues 8 were the first to demonstrate the association between LNR and survival rate in patients with rectal cancer. The mean LNR was 0.34, and they reported that LNR was an independent risk factor for local recurrence, DFS and OS.…”
mentioning
confidence: 99%
“…The mean LNR was 0.34, and they reported that LNR was an independent risk factor for local recurrence, DFS and OS. In these studies, [4][5][6][7][8] 9 According to the seventh edition of the TNM classification, patients with stage III cancer are classified based on the number of positive nodes. Intuitively, it seems safe to believe that the prognostic significance of 5 positive nodes out of a total of 5 will be completely different from 5 positive nodes out of a total of 30.…”
mentioning
confidence: 99%